Short-term predictive value of sST2 in patients with STEMI following primary PCI: a prospective observational study - Shan Huang; Lu-Jiao Yu; Guang-Feng Sun; Zi-Xin Zhang (BMC Cardiovascular Disorders)
Abstract Aim The objective of this study was to investigate the level of soluble suppression of tumorigenicity-2 (sST2) in patients with acute ST-segment elevation myocardial infarction (STEMI) following primary percutaneous coronary intervention (PCI), and to provide a new biomarker for clinical management and prognosis assessment. Method This was a prospective study. 148 STEMI patients following primary PCI were enrolled and divided into 2 groups by the median value of sST2 and afterwards followed up for 30 days to access the occurrence of major adverse cardiac events (MACEs), which were defined as cardiovascular death, heart failure and recurrent MI. Results sST2 ranged from 20.57 to 98.96 ng/mL. High sST2 group had higher MACEs rate compared to low sST2 group (28.8% vs. 8.0%, P = 0.001). sST2 was positively correlated with age (r = 0.181, P = 0.027), SYNTAX score (r = 0.257, P = 0.002), high-sensitive C-reactive protein (hs-CRP) (r = 0.225, P = 0.006), B-type natriuretic peptide (BNP) (r = 0.225, P = 0.006) and negatively with left ventricle ejection fraction (LVEF) (r = -0.197, P = 0.016). After adjustment for clinical variables, sST2 level (OR 3.680, P = 0.015) and LVEF (OR 0.880, P < 0.001) remained independent predictors of 30-days MACEs. In receiver operating characteristic curve (ROC) analyses, the area under the curve (AUC) of sST2 for predicting 30-days MACEs was 0.755(P < 0.001). The AUC of sST2 combining hs-CRP and LVEF for prediction was 0.828(95%CI [0.743–0.912], P < 0.001). Conclusion sST2 level after primary PCI was an independent risk factor of MACEs in STEMI patients through 30 days follow-up.